Molecular and epidemiological characterization of Coxsackievirus A6 causing hand, foot and mouth disease in the Philippines from 2012 to 2017 - Foronda, Janiza Lianne M.; Climacosa, Fresthel Monica M. (Manila College of Public Health, University of the Philippines Manila, 2021)
Background: Hand, foot, mouth disease (HFMD) is a self-limiting diseased characterized by lesions om hand, foot, and mouth, which may extend to other body parts or may lead to severe complications. Enteroviruses, particularly CV-A6 have been reported to be predominant cause of this disease worldwide.

Objectives: The study aimed to determine the molecular and epidemiological characteristics of CV-A6 among confirmed HFMD cases in the Philippines from 2012-2017. Specifically, the study intended to determine the (1) demographic and clinical profiles of these cases; (2) circulating lineages of CV-A6 based on the phylogenetic analysis of the VP1 gene; and, (3) presence of CV-A6 recombinants by analyzing the of VP 1 and 3Dpol gene regions.

Methods: Laboratory confirmed CV-A6 positive HFMD cases from 2012-2017 were analyzed for the study. Demographic and clinical profiles were derived from Hand-Foot-and-Mouth Disease and Severe Enteroviral Disease Surveillance records obtained with permission from the National Poliovirus and other Enteroviruses Reference Laboratory. Randomly selected samples positive for Cv-A6 were characterized according to their virus protein 1 (VP1) and 3D polymerase (3Dpol) encoding gene sequence using RT-PCR , sequencing, and phylogenetic analysis.

Results: In this study, we determine that majority of the cases infected were under 3 years old (69.2%) with few cases occurring in adults. Phylogenetic analysis of partial VP1 and 3Dpol regions reveal the dominance and nationwide circulation of recombinant CV-A6 from lineage E2, under RF-A. Complications and other findings associated with CVA-6 are mainly respiratory-related morbidities.

Conclusions: The results of the study emphasize the need for close monitoring of HFMD serotypes, particularly viruses similar to CV-A6, which is associated with altered clinical phenotypes according to emerging lineages and recombinants forms. A comprehensive view of the clinical spectrum and epidemiology of CV-A6-associated HFMD is presented in order to contribute in the entire picture of HFMD in the Philippines and aid in formulating effective intervention strategies, outbreak response, and contribute to the development of an effective HFMD vaccine.
Includes references and appendices.
Master's Thesis
Keywords: Coxsackievirus A6 -- Molecular epidemiology -- Philippines; Hand-foot-and-mouth disease -- Epidemiology -- Philippines; Hand-foot-and-mouth disease -- Virology -- Philippines; Virus diseases -- Molecular diagnosis -- Philippines; Enterovirus infections -- Epidemiology -- Philippines